Assessment of learning outcomes for online and offline modes of teaching: A comparative study - K E GANESH (IJRDO- Journal of Educational Research, 2022)
Due to Nationwide lockdown of all sectors which was announced from 24th March 2020 to 31st May 2020 due to COVID-19 pandemic, the only option that was available for education sector is to continue the process of teaching & learning through online platform. Each platform whether it is offline or online has its own merits and drawbacks. The learning outcomes of the students are being defined in the form of course outcomes (CO). The CO’s have been assessed in the subject of Applied Physics for the students of first year Bachelor of Engineering (BE) for both offline & online platform. In the present study, improvement in the students’ performance (theory/written type of evaluation)  in the form of attainment of the defined CO’s in online platform is observed to be 85% and above. However, the performance got reduced to 4.81% in laboratory examination as more weightage was given to Viva-Voce (verbal questioning) type of evaluation. A detailed analysis of the students’ performance along with possible conclusions have been presented in this article.